Comparing the Economic Efficiency of Two and Three Rice Crops per Year in Chau Phu District, An Giang Province - Dut, Vo Van; Nhan, Nguyen Chinh; Thuan, Nguyen Xuan (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 34 No 3, 2018)
The aim of this study is to compare the economic efficiency between two and three rice crops per year in Chau Phu District, An Giang Province. Additionally, the study examines the determinants of economic efficiency of the two patterns by using multiple regression. Data was collected by interviewing directly farmers producing two and three rice crops per year in Chau Phu District, An Giang Province. The results reveal that the economic efficiency of two rice crops per year is higher than that of three rice crops per year. Labor, fertilizer, land preparation, pesticide and harvest costs and rice price strongly affect the economic efficiency of the two patterns.